2016
DOI: 10.1021/acs.jnatprod.6b00011
|View full text |Cite
|
Sign up to set email alerts
|

Melokhanines A–J, Bioactive Monoterpenoid Indole Alkaloids with Diverse Skeletons fromMelodinus khasianus

Abstract: The new melokhanines A-J (1-10) and 22 known (11-32) alkaloids were isolated from the twigs and leaves of Melodinus khasianus. The new compounds and their absolute configurations were elucidated by extensive analysis of spectroscopic, X-ray diffraction, and computational data. Melokhanine A (1), composed of a hydroxyindolinone linked to an octahydrofuro[2,3-b]pyridine moiety, is an unprecedented monoterpenoid indole alkaloid. Melokhanines B-H (2-8) possess a new 6/5/5/6/6 pentacyclic indole alkaloid skeleton. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 59 publications
0
46
0
Order By: Relevance
“…In this study, 15 monoterpenoid indole alkaloids were isolated and identified. According to the structural characteristics, the compounds were classified as strychnos-type alkaloids (1-3), aspidosperma-type alkaloids (4)(5)(6)(7)(8), condylocarpan-type alkaloid (9), eburna-type alkaloids (10)(11), and quinoline-type alkaloids (12)(13)(14)(15). Previous reports on the cytotoxic activities of the compounds showed that aspidosperma-type alkaloids 4, 5, 6 and 8 had significant cytotoxic activities on human cancer cell lines, while other types of compounds have no obvious cytotoxic activity [13,19].…”
Section: Aggregationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 15 monoterpenoid indole alkaloids were isolated and identified. According to the structural characteristics, the compounds were classified as strychnos-type alkaloids (1-3), aspidosperma-type alkaloids (4)(5)(6)(7)(8), condylocarpan-type alkaloid (9), eburna-type alkaloids (10)(11), and quinoline-type alkaloids (12)(13)(14)(15). Previous reports on the cytotoxic activities of the compounds showed that aspidosperma-type alkaloids 4, 5, 6 and 8 had significant cytotoxic activities on human cancer cell lines, while other types of compounds have no obvious cytotoxic activity [13,19].…”
Section: Aggregationsmentioning
confidence: 99%
“…Alkaloid is one of the most important classes of plant natural products with a large range of therapeutic properties, including anti-depressant, immunosuppressive, antimicrobial, anti-inflammatory, anti-tumor, etc. [4][5][6]. Some of which have been developed as clinical drugs to treat a variety of illnesses [7].…”
Section: Introductionmentioning
confidence: 99%
“…Indolin‐3‐ones with a N ‐fused ring as an important kind of heterocycles have unique biological and pharmaceutical activities which exist as core scaffold in a number of natural products, such as (–)‐isatisine A, (–)‐melokhanine E, fluorocarpamine (Figure ). Thus, the methods for the synthesis of indolin‐3‐ones containing a N ‐fused ring have been reported extensively Among those reported reactions, the substituted 2‐aryl‐3 H ‐indol‐3‐ones G were used as the key substrates, which could be attacked easily by various nucleophilic reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Within the family, melokhanine E is of particular interest due to its superior, broad-spectrum activity (MIC = 2 µM against P. aeruginosa and 5 µM against E. faecalis). 4 A key structural motif of the melokhanines is a core piperidine heterocycle bearing C3 quaternary substitution. This structural element is found in an array of bioactive natural products and represents a significant synthetic challenge (2-5, Figure 1).…”
mentioning
confidence: 99%
“…With the natural product in hand, we next sought to confirm the biological activity reported in Luo and coworkers' isolation report. 4 In the isolation report, Luo and coworkers report impressive antibiotic against gram-negative bacteria (P. aeruginosa MIC 2 µM, 0.78 µg/mL) as well as gram-positive bacteria (E. faecalis MIC 5 µM, 1.56 µg/mL). We explored the activity of 1 against both the pathogens reported in the isolation report as well as the ATCC numbers reported 22 and found in all cases the activity of the natural product was > 256 µg/mL.…”
mentioning
confidence: 99%